Eye blink in newborn and preschool-age children - Lavezzo, Marcelo M.; Schellini, Silvana Artioli [UNESP]; Padovani, Carlos Roberto [UNESP]; Hirai, Flavio Eduardo (Blackwell Publishing, 2008)
Purpose: To investigate the dynamics of ocular eyelid movements in newborn infants and preschool-age children.Methods: Fifty newborn infants and 200 preschool children aged 4-6 years were examined. Images of each child, with his or her eyes in the primary eye position looking at an object placed at the child's height, were recorded with a digital videocamera for 3 mins. Complete and incomplete blink rates, opening, closing and complete blink times were calculated.Results: Newborn infants presented a lower number of incomplete movements than preschool children. The complete blink rate was lower in newborn infants (6.2 blinks/min) than in preschool children (8.0 blinks/minute). Eyelid closing, opening and compete blink times were longer in newborn infants than in preschool children at all observation times.Conclusions: Newborn infants had a different pattern of eyelid movement compared with preschool children. Specific characteristics that are found in this group of children particularly, such as immaturity of the neural system and more resistant tear film, may explain these findings in part.
Keywords: eye blink; newborn; preschool children; eyelid closing time; eyelid opening time; digital image